If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -2(x + 7) = 4(2x + -1) Reorder the terms: X + -2(7 + x) = 4(2x + -1) X + (7 * -2 + x * -2) = 4(2x + -1) X + (-14 + -2x) = 4(2x + -1) Reorder the terms: -14 + X + -2x = 4(2x + -1) Reorder the terms: -14 + X + -2x = 4(-1 + 2x) -14 + X + -2x = (-1 * 4 + 2x * 4) -14 + X + -2x = (-4 + 8x) Solving -14 + X + -2x = -4 + 8x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '14' to each side of the equation. -14 + X + 14 + -2x = -4 + 14 + 8x Reorder the terms: -14 + 14 + X + -2x = -4 + 14 + 8x Combine like terms: -14 + 14 = 0 0 + X + -2x = -4 + 14 + 8x X + -2x = -4 + 14 + 8x Combine like terms: -4 + 14 = 10 X + -2x = 10 + 8x Add '2x' to each side of the equation. X + -2x + 2x = 10 + 8x + 2x Combine like terms: -2x + 2x = 0 X + 0 = 10 + 8x + 2x X = 10 + 8x + 2x Combine like terms: 8x + 2x = 10x X = 10 + 10x Simplifying X = 10 + 10x
| 7ysqared=112 | | 100+x=12x+1 | | 3squared+24=88 | | 6+18y= | | 12(x+8)=10x+16 | | 2x-4n-8=0 | | 8x+5=10x-5 | | 0.66x-5=2x | | 3(x-4)=-4+44 | | 15+3n=27 | | -6=-4-2x | | -8x(x+1)=4(x-11) | | 4x+1=5j-1 | | y=x^2+60x-300 | | 4(3+3x)-2=70 | | x+(x+5)=69 | | 22x=25x-6 | | 6(2n-1)=2(5n-3)+4n | | 9y+1=8y-2 | | (u-7)(u+1)= | | 3(a-5)+7=-2 | | 3x^2-21x-36=0 | | -3(6-2t)=-48 | | 8z^2+20z-49=0 | | 5x+15-2x=25+3x-10 | | 5log(x+3)=12 | | 5x=42-3x | | x^2-6+3x^2-10x+2= | | 6x-1=-2(3-5x) | | 7=(t-1)-2(t-3) | | 9+3x=-(x+7) | | 16-x=4+5x |